The Humanism of Ancient Chinese Shuyuan and Its Enlightenment to Modern Higher Education - Zhang, Yan; Fang, Yanhong (Education Insights, 2026)
Ancient Chinese Shuyuan (traditional academies) represents a unique and highly influential educational institution, serving as an indispensable carrier for the historical inheritance and continuous evolution of Chinese culture. At its cultural core, the Shuyuan system is profoundly anchored in humanism. Nourished predominantly by classical Confucianism, this inherent humanism manifests prominently across four fundamental dimensions: the foundational educational principle of prioritizing moral virtue above all else, the cultivation of an inclusive and remarkably open educational philosophy, the profound educational wisdom demonstrated through deliberate environment-shaping, and the establishment of a deeply harmonious, mutually respectful teacher-student relationship. Since the dawn of modern times, accompanied by the formal abolition of the traditional Shuyuan system and the subsequent rapid rise of Western-style modern education, a profound cultural discontinuity has unfortunately occurred within the broader Chinese cultural tradition. This rupture has led to a significant loss of indigenous pedagogical wisdom. Therefore, systematically reviving the core tenets and structural system of Shuyuan within the framework of modern higher education to effectively bridge this historical and cultural discontinuity is of immense practical value. Such a revival not only facilitates the comprehensive reform and sustainable development of contemporary Chinese higher education but also fosters a more holistic, culturally resonant approach to cultivating modern talents equipped with both professional expertise and profound moral integrity.